Implementing the ten-group-classification-system of caesarean section at Good Hope Hospital (UK) FOR 2008. (16th November 2010) - Chan, JCY; Honest, H
Abstract : Background: The Ten-Group-Classification-System (TGCS) categorises each birth into one of 10 mutually exclusive but totally inclusive and clinically relevant groups.1 It is simple to apply and permits subgroup analysis of Caesarean section rates (CSR) over time for comparison within and between institutions. Its implementation should precede the debate what constitutes an appropriate CSR for a unit.2 3 Method: The authors conducted a retrospective audit of our institution CSR by applying TGCS to all registerable births in 2008. Information was retrieved from birth and theatre registers, and electronic birth registration. Data were analysed using Excel and STATA 8.2. Results: A total of 3245 women (mean age 29±6.4 years, 44.5% nulliparous) gave birth to 3296 babies in 2008. Groups overall CSR was 25.0% (range 4.0–100%). The three main contributors to overall CSR (59% of all CS) were: nulliparous term cephalic singleton in spontaneous labour (TGCS-1, CSR 11.4%) and not in spontaneous labour (TGCS-2, CSR 39.3%), and term cephalic singleton with previous CS (TGCS-5, CSR 82.1%). Numerically emergency CS for TGCS-1 and 2 outnumbered CS performed for other groups including those with previous CS. When comparing spontaneous and induced labour in subgroups analysis, induction was shown to consistently increase CSR by two- to threefolds. Conclusion: TGCS defined CSR for our heterogeneous obstetric caseload. It highlighted specific groups with high CSR to target resources for CSR reduction intervention. The authors recommend that institutions seeking to address their CSR should utilise this standard, simple and informative tool without delay.